2002
DOI: 10.2355/isijinternational.42.751
|View full text |Cite
|
Sign up to set email alerts
|

The Deformation Microstructure and Recrystallization Behavior of Warm Rolled Steels.

Abstract: The deformation microstructure of various warm (ferritic) rolled steels was characterized and its influence upon the subsequent annealing behavior determined. The materials investigated included three interstitialfree (IF) steels (stabilized with either titanium or niobium), an extra low carbon (ELC) steel, and four experimental low carbon chromium steels with varying levels of boron, nitrogen and phosphorus. Single pass rolling experiments were conducted in a pilot mill at temperatures between 440 and 850°C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 12 publications
(22 reference statements)
2
16
2
1
Order By: Relevance
“…It is clear that, according with calculations, the whole amount of P and a significant amount of Ti remains in solid solution in the ferrite. However, it has been profusely reported in literature 25,26) that in presence of Ti, P forms FeTiP phosphide which leads to the deterioration of both drawability and loss of strength. The FeTiP precipitates present in IF-HR steel (Fig.…”
Section: Precipitation Statementioning
confidence: 99%
“…It is clear that, according with calculations, the whole amount of P and a significant amount of Ti remains in solid solution in the ferrite. However, it has been profusely reported in literature 25,26) that in presence of Ti, P forms FeTiP phosphide which leads to the deterioration of both drawability and loss of strength. The FeTiP precipitates present in IF-HR steel (Fig.…”
Section: Precipitation Statementioning
confidence: 99%
“…18) ................. (13) where k s is the shear yield stress, v r the relative velocity between the tool and the deforming metal, m the friction factor, and a is a positive constant of the order of 10 Ϫ4 . Equations (2), (10) and (11) should be solved simultaneously to have the temperature distribution, the velocity field and the kinetics of dynamic recovery. In order to solve the heat conduction and the energy equations, a two dimensional finite element analysis utilizing four-node isoparametric elements 19) are employed and Newton-Raphson and direct iteration methods are used to solve the nonlinear system of…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Flow stress modelling under warm rolling conditions has been carried out by Huang et al 9) In this research, two grades of commercial Ti-Nb stabilized interstitial free steels were investigated and a flow stress model with regard to dynamic recovery and recrystallization was developed to predict flow behavior of steels during warm rolling. The microstructure and recrystallization kinetics after warm rolling was studied by Liu et al 10) They have shown that dynamic strain aging could be responsible for the formation of moderate and intense shear bands in IF and low carbon steels, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence of shear band morphology and intensity on rolling temperature in these steels has been described in detail in Ref. 21). Barnett and Jonas 1,22) stressed that this dependence can be linked directly to the DSA behaviors of these materials.…”
Section: Effect Of Solute Carbonmentioning
confidence: 99%